Kontrowersje wokół kulturowych (re)adaptacji języka angielskiego – przykład Japonii - Gromkowska-Melosik , Agnieszka (Studia Edukacyjne, 2017)
The article is aimed at reconstructing the selected problems of English language adaptation in Japanese society. The author is convinced that there is a whole range of phenomena and paradoxes in Japan that fit perfectly the dilemma of cultural and national controversies around the English as a global language and around the concept of cultural imperialism. The main tension is connected with the fact that such societies as Japan want to keep their own mono-ethnicity and it is obvious that one of the most important components of it is native language treated as a form of embodiment of Japanese values and traditions. So, English is a threat to monolith of Japanese nation. On the other hand Japanese are aware that English helps their nation to rise the chance in global competition in global markets as well as it connects Japan to the world culture.